2007
DOI: 10.1016/j.plefa.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Heparin, lipoproteins, and oxygenated fatty acids in blood: A cautionary note

Abstract: We measured 16 nonesterified oxygenated fatty acid derivatives (oxylipids) in plasmas from 7 human subjects. Two arterial samples from each subject were analyzed, drawn approximately two hours apart. We observed a marked increase in levels of most oxylipids in the second sample, as high as 470 fold. Between the first and second sample, subjects received approximately 800-1,000 IU of heparin to prevent clotting in intravascular catheters. We postulate that heparin activated lipoprotein lipases, which, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The observed concentration of hydroxy-, epoxy- and dihydroxy-FA in serum were well in line with previously described levels of these oxylipins in plasma [11]. The oxylipin concentration in plasma can be strongly effected by the anticoagulant used [45]. Serum is a standard matrix which is used for the analysis of many biochemical parameters in blood and can be obtained in highly reproducible quality.…”
Section: Discussionsupporting
confidence: 87%
“…The observed concentration of hydroxy-, epoxy- and dihydroxy-FA in serum were well in line with previously described levels of these oxylipins in plasma [11]. The oxylipin concentration in plasma can be strongly effected by the anticoagulant used [45]. Serum is a standard matrix which is used for the analysis of many biochemical parameters in blood and can be obtained in highly reproducible quality.…”
Section: Discussionsupporting
confidence: 87%
“…In the VLDL fractions used for HAEC treatments, the LA-derived oxidized lipids 13-HODE and 9-HODE were elevated .10-fold, whereas LA increased ?3-fold during the 30 min lipolysis process. In a recent study, Goodfriend et al (58) observed a remarkable increase in nonesterified oxylipids in plasma from subjects who received heparin, suggesting that human TGRLs contain these oxidized lipids in vivo, as observed in rats (51). Therefore, it appears that significant amounts of oxidized lipids are released during TGRL lipolysis, and may be involved in eliciting responses in exposed endothelium.…”
Section: Discussionmentioning
confidence: 95%
“…A particular issue related to the measure of oxylipins in blood is the potential effects of the blood collection process as well as serum/plasma generation upon the observed oxylipin profile . Accordingly, it is essential that blood collection, processing, and handling methods are reported in detail when providing oxylipin data.…”
Section: Discussionmentioning
confidence: 99%